2017
DOI: 10.1016/j.trc.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Mining factors affecting taxi drivers’ incomes using GPS trajectories

Abstract: Taxis provide essential transport services in urban areas. In the taxi industry, the income level remains a cause of concern for taxi drivers as well as regulators. Mining underlying factors affecting the income level will not only benefit the newcomers and low-income drivers but also assist in developing effective optimization algorithms for taxi operations. This paper intends to disclose the factors affecting incomes along with their quantitative influence by mining over 167 million GPS records from nearly 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…Kong et al[ 23 ] proposed a time-location-relationship (TLR) model to predict passenger distribution for different social functional regions. Qin et al [ 24 ] applied a multilevel ordered logit model to investigate the significant factors that influence taxi driver’s incomes using data from 8,000 taxis in Shanghai. Yamamoto et al [ 25 , 26 ]developed an adaptive routing method to help taxi drivers acquire passengers more effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kong et al[ 23 ] proposed a time-location-relationship (TLR) model to predict passenger distribution for different social functional regions. Qin et al [ 24 ] applied a multilevel ordered logit model to investigate the significant factors that influence taxi driver’s incomes using data from 8,000 taxis in Shanghai. Yamamoto et al [ 25 , 26 ]developed an adaptive routing method to help taxi drivers acquire passengers more effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies worked further to improve understanding of these taxi operation patterns, including taxi demand distribution predicting in order to recommend the best queuing locations for taxi drivers [24,25]. Aided by GPS data, Gao et al [25] and Qin et al [26] investigated the differences in drivers' operation strategies and revealed the top drivers' strategies to help ordinary drivers increase their incomes.…”
Section: Assessment Of Taxi Service and Operationsmentioning
confidence: 99%
“…In Shanghai, taxi trips are highly concentrated within the downtown area bounded by the Outer Ring Road, where about 82.25% of taxi pickups are generated, which makes it an appealing choice for our study area [26]. To facilitate the investigation of spatial variations of taxi operations, we segment the study area into small square cells with dimensions of 1 km × 1 km.…”
Section: Study Area and Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid expansion of online ride-hailing services, many conflicts of interests between online ride-hailing vehicles and traditional taxis have appeared and are becoming increasingly acute [5]. These conflicts result in shrinking of the traditional taxi market [6] and decline in the income of taxi drivers [7]. Meanwhile, many violent incidents have broken out between traditional taxi drivers and online ride-hailing drivers [8].…”
Section: Introductionmentioning
confidence: 99%